The Social Context of Homeless Women’s Alcohol and Drug Use - Wenzel, Suzanne L. (2009)
BACKGROUND: Substance use poses a significant threat to the health of women, and homeless women are more likely to use alcohol and drugs than other women. Addressing risk factors in this population requires a focus on the social context of substance use among homeless women. METHODS: Participants were 445 homeless women who were randomly sampled and interviewed in shelter settings about the characteristics of their personal networks. Binomial logistic regressions predicted days of binge drinking and of using marijuana, crack, cocaine, and methamphetamine or other amphetamines in the past 6 months. RESULTS: Homeless women with a greater proportion of heavy alcohol users in their personal networks had greater odds of engaging in binge drinking, and women with a greater proportion of drug users in their networks had greater odds of using marijuana, cocaine, crack, and methamphetamine or other amphetamines. Women with a greater proportion of individuals in their networks that they had met in school or through work had lower odds of marijuana, cocaine, and crack use. CONCLUSIONS: Findings suggest the importance of structural solutions in addressing homeless women’s alcohol and drug use, including greater access to treatment and recovery support for alcohol and drug problems as well as depression, and enhancing employment and educational, opportunities for homeless women.